Functionality of Web-Based E-Journal Publishing Environment - Ainnecia, Yoag (2004)
Journal has become important information sources, and can be found in many forms including printed and digitized Electronic journal (e-journal) publishing provides lots of advantages such as a solution to expedite the journal publishing process. This project identifies and validates the functionalities of a Web-based e-journal publishing environment in three different perspectives : readers, authors and editors. A prototype was built and futher tested by potential users to validate the identified funtionalities. The prototype was developed using PHP programming language together with MySQL as its database. Nineteen main functionalities were listed, of which two are for the readers, nine for the authors and eight for the editors. Comments from participants indicate that the prototype performed accordingly to their expectation and the provided functionalities managed to expedite submission and publishing process. Few recommendations to enhance the system were also noted.